Cultural Elements of the Sundanese Community Group Judging from Sociology - Tony Tedjo; Tjutjun Setiawan; Fery Rondonuwu; Sri Darajad Suaji; Normando Justine Aulia (Budapest International Research and Critics University, 2021)
This journal was arranged using a descriptive qualitative method, in which the authors of the journal collected research materials from literature sources in the form of books, journals, and several statistical sources and then combined them into a unified whole in this journal. Broadly speaking, it will be explained about the cultural elements of the Sundanese community group based on the seven points of review of cultural elements proposed by Kroeber & Kluckhonhn, namely: (1) tools and equipment for human life, (2) livelihood and economic system, (3) social system, (4) language, (5) art, (6) knowledge system, and (7) religion.